Light-emitting device, preparation method and display device
By introducing an interface modification layer and a hole functional layer of the metal nanocone array structure into the light emitting device, the problem of difficulty in injecting holes into the light emitting layer is solved, and the brightness and carrier injection efficiency of the light emitting device are improved.
Patent Information
- Application Number
- CN202311283839.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-28
- Publication Date
- 2024-12-27
AI Technical Summary
The selection of hole transport layer materials in existing light emitting devices makes it difficult for holes to be injected into the light emitting layer, resulting in lower brightness of the device.
A light emitting device structure is adopted that includes an interface modification layer and a hole functional layer, wherein the interface modification layer is composed of a metal protrusion and an interface body, and the metal protrusion faces the light emitting layer, combining a hole transport layer and a hole injection layer, using a metal nanocone The array structure improves hole injection efficiency.
The metal nanocone array structure in the interface modification layer generates plasma excitation, enhances the electromagnetic field, promotes hole injection, improves device brightness and carrier injection balance, and improves hole transmission efficiency.
Smart Images

Figure CN119212421A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of light-emitting devices, and more specifically, to a light-emitting device and a preparation method thereof, and a display device. Background Art
[0002] In the light-emitting devices of the prior art, the materials used to prepare the hole transport layer are usually TFB, PVK, etc., holes are difficult to be injected into the light-emitting layer, and the hole transport efficiency is low, resulting in low brightness of the device. Summary of the invention
[0003] Based on this, an object of the present invention is to provide a light-emitting device and a method for preparing the same, and a display device.
[0004] In order to achieve the above object, the present invention provides a light-emitting device, comprising a first electrode, an interface modification layer, a light-emitting layer, and a second electrode stacked in sequence; the interface modification layer comprises an interface body and a metal protrusion.
[0005] Optionally, in some embodiments of the present application, the metal protrusion is arranged on the surface of the interface body on a side close to the light-emitting layer; and / or
[0006] The materials of the interface body and the metal protrusion are independently selected from one or more of gold, silver, and platinum group metals, and the platinum group metals include one or more of iridium, rhodium, palladium, and platinum.
[0007] Optionally, in some embodiments of the present application, the light-emitting device further comprises a hole functional layer, wherein the hole functional layer is disposed between the first electrode and the light-emitting layer, the interface modification layer is disposed on the surface of the hole functional layer on a side close to the light-emitting layer, and the convex surface of the metal protrusion faces the light-emitting layer; and / or
[0008] The hole functional layer includes a hole transport layer and / or a hole injection layer; the hole transport layer or the hole injection layer is arranged between the first electrode and the interface modification layer; when a hole injection layer is arranged, the hole injection layer is arranged between the first electrode and the interface modification layer, and the hole transport layer is arranged between the hole injection layer and the interface modification layer; and / or
[0009] The metal protrusions include regular-shaped protrusions and irregular-shaped protrusions, and the regular-shaped protrusions include one or more of metal nano-conical protrusions, metal nano-hemispherical protrusions, metal nano-curved surface protrusions, metal nano-truncated cone protrusions, metal nano-wedge-shaped protrusions, and metal nano-polygonal protrusions; and / or
[0010] The light-emitting device further comprises an electron transport layer disposed between the light-emitting layer and the second electrode; and / or
[0011] The diameter of the luminescent nanoparticles in the luminescent layer is 5-10 nm.
[0012] Optionally, in some embodiments of the present application, the average height of the metal protrusions is 10-20 nm; and / or
[0013] The average distance between the tops of two adjacent metal protrusions is 20-300 nm; and / or
[0014] The average diameter or average equivalent diameter of the metal protrusions close to the interface body is 5-10 nm; and / or
[0015] The average diameter or average equivalent diameter of the metal protrusions in the projected area on the interface body is 5-10 nm; and / or
[0016] The metal nano-cone-shaped protrusions include metal nano-cone-shaped protrusions and metal nano-pyramid-shaped protrusions, and the metal nano-hemispherical protrusions also include metal nano-semi-ellipsoidal protrusions.
[0017] Optionally, in some embodiments of the present application, the hole transport layer comprises alternating layers of different types of nanosheets; wherein the different types of nanosheets comprise nanosheets of different thicknesses and / or nanosheets of different materials; and / or
[0018] The material of the nanosheet includes a two-dimensional material; wherein the two-dimensional material includes one of graphene, boron nitride, molybdenum disulfide, carbon nanotubes, fullerenes, carbon nanosheets, tungsten disulfide, molybdenum diselenide, tungsten diselenide, and MXene; and / or
[0019] The thickness of the nanosheet is 3-4 nm.
[0020] Optionally, in some embodiments of the present application, the hole transport layer is composed of two different types of nanosheets stacked alternately. Optionally, in some embodiments of the present application, the first electrode and the second electrode independently include a doped metal oxide particle electrode, a composite electrode, a graphene electrode, a carbon nanotube electrode, a metal element electrode or an alloy electrode, the material of the doped metal oxide particle electrode includes one or more of indium-doped tin oxide, fluorine-doped tin oxide, antimony-doped tin oxide, aluminum-doped zinc oxide, gallium-doped zinc oxide, indium-doped zinc oxide, magnesium-doped zinc oxide and aluminum-doped magnesium oxide, the composite electrode includes one or more of AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, TiO2 / Ag / TiO2, TiO2 / Al / TiO2, ZnS / Ag / ZnS or ZnS / Al / ZnS, and the material of the metal element electrode includes one or more of Ag, Al, Cu, Mo, Au, Pt, Ca, Mg and Ba; and / or
[0021] The material of the electron transport layer includes inorganic materials and / or organic materials; the inorganic material includes one or more of doped or undoped zinc oxide, barium oxide, nickel oxide, titanium oxide, tin oxide, tantalum oxide, zirconium oxide, nickel oxide, lithium titanium oxide, zinc aluminum oxide, zinc manganese oxide, zinc tin oxide, lithium zinc oxide, indium tin oxide, cadmium sulfide, zinc sulfide, molybdenum sulfide, tungsten sulfide, copper sulfide, zinc tin, indium phosphide, gallium phosphide, copper indium sulfide, copper gallium sulfide, and barium titanate, and the doped element includes one or more of aluminum, magnesium, lithium, manganese, yttrium, lanthanum, copper, nickel, zirconium, cerium, and gadolinium; the organic material includes one or more of quinoxaline compounds, imidazole compounds, triazine compounds, fluorene compounds, and hydroxyquinoline compounds; and / or
[0022] The material of the light-emitting layer includes one or more quantum dot light-emitting materials, and the quantum dot light-emitting materials include one or more of single-structure quantum dots, core-shell quantum dots and perovskite semiconductor materials. The material of the single-structure quantum dots, the core material of the core-shell quantum dots and the shell material of the core-shell quantum dots respectively include at least one of II-VI group compounds, IV-VI group compounds, III-V group compounds and I-III-VI group compounds. The II-VI group compounds include CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSe At least one of Te, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe, and the IV-VI group compound includes SnS, SnSe, SnTe, PbS, PbSe, PbTe , SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe, SnPbSTe, and the III-V group compound includes GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, In At least one of NSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs and InAlPSb, the I-III-VI group compound includes at least one of CuInS2, CuInSe2 and AgInS2, and the perovskite semiconductor material includes a doped or undoped inorganic perovskite semiconductor or an organic-inorganic hybrid perovskite semiconductor. The inorganic perovskite semiconductor has a general structural formula of AMX3, wherein A is Cs + ions, M is a divalent metal cation, including Pb 2+ Sn 2+, Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ At least one of X is a halogen anion including Cl - Br - ,I - The general structural formula of the organic-inorganic hybrid perovskite semiconductor is BMX3, wherein B is an organic amine cation, including CH3(CH2) n-2 NH3 + or [NH3(CH2) n NH3] 2+ , where n≥2, M is a divalent metal cation, including Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ At least one of X is a halogen anion including Cl - Br - ,I - At least one of; and / or
[0023] The hole functional layer also includes a hole injection layer, and the material of the hole injection layer includes 4,4'-N,N'-dicarbazolyl-biphenyl, N,N'-diphenyl-N,N'-bis(1-naphthyl)-1,1'-biphenyl-4,4"-diamine, N,N'-diphenyl-N,N'-bis(3-methylphenyl)-(1,1'-biphenyl)-4,4'-diamine, N,N'-bis(3-methylphenyl)-N,N'-bis(phenyl)-spiro, N,N'-bis(4-(N,N'-diphenyl-amino)phenyl)-N,N'-diphenylbenzidine, 4 , 4',4'-tri(N-carbazolyl)-triphenylamine, 4,4',4'-tri(carbazolyl-9-yl)triphenylamine, trichloroisocyanuric acid, terbium-doped phosphate-based green luminescent materials, 2,3,6,7,10,11-hexacyano-1,4,5,8,9,12-hexaazatriphenylene, 4,4',4'-tri(N-3-methylphenyl-N-phenylamino)triphenylamine, poly[(9,9'-dioctylfluorene-2,7-diyl)-co-(4,4'-(N-(4-sec-butylphenyl)diphenylamine))], poly(4-butylphenyl-diphenylamine)(poly -TPD), poly[bis(4-phenyl)(4-butylphenyl)amine], polyaniline, polypyrrole, poly(p-phenylene vinylene), poly(phenylene vinylene), poly[2-methoxy-5-(2-ethylhexyloxy)-1,4-phenylene vinylene] and poly[2-methoxy-5-(3',7'-dimethyloctyloxy)-1,4-phenylene vinylene], copper phthalocyanine, aromatic tertiary amines, polynuclear aromatic tertiary amines, 4,4'-bis(p-carbazolyl)-1,1'-biphenyl compounds, N,N,N',N'-tetraarylbenzidine, PEDOT, PED At least one of OT:PSS and its derivatives, PEDOT:PSS derivatives doped with s-MoO3, poly(N-vinylcarbazole) (PVK) and its derivatives, polymethacrylate and its derivatives, poly(9,9-octylfluorene) and its derivatives, poly(spirofluorene) and its derivatives, N,N'-di(naphthalene-1-yl)-N,N'-diphenylbenzidine, spiro NPB, nano-polycrystalline diamond, microcrystalline cellulose, tetracyanoquinodimethane, doped graphene, undoped graphene, C60, transition metal oxides, transition metal sulfides, and transition metal tin compounds.
[0024] The present application provides a method for preparing a light-emitting device, comprising the following steps:
[0025] providing a first electrode;
[0026] forming a hole functional layer on the first electrode;
[0027] Forming the interface modification layer in the light-emitting device as described above on the hole functional layer;
[0028] forming a light-emitting layer on the interface modification layer;
[0029] A second electrode is formed on the light-emitting layer to obtain a light-emitting device.
[0030] Optionally, in some embodiments of the present application, the hole functional layer includes a hole transport layer and / or a hole injection layer; the hole transport layer or the hole injection layer is arranged between the first electrode and the interface modification layer; or
[0031] The hole injection layer is disposed between the first electrode and the interface modification layer, and the hole transport layer is disposed between the hole injection layer and the interface modification layer; and / or
[0032] The interface modification layer comprises an interface body and a metal protrusion, wherein the convex surface of the metal protrusion faces the light-emitting layer; and / or
[0033] An electronic functional layer is further provided between the light-emitting layer and the second electrode, and the electronic functional layer includes an electron transport layer.
[0034] Optionally, in some embodiments of the present application, the first electrode is configured as an anode and the second electrode is configured as a cathode; or, the first electrode is configured as a cathode and the second electrode is configured as an anode.
[0035] Optionally, in some embodiments of the present application, the method for preparing the interface modification layer comprises the following steps:
[0036] Setting a template etching layer;
[0037] Prepare metal protrusions by etching the layer through the template;
[0038] The template etching layer is removed to obtain a layer including at least one metal protrusion, namely, an interface modification layer.
[0039] Optionally, in some embodiments of the present application, the template etching layer includes a microsphere layer, and the microsphere layer includes one or more of a self-assembled polystyrene microsphere layer and a self-assembled silica microsphere layer.
[0040] Optionally, in some embodiments of the present application, the method for preparing the self-assembled polystyrene microsphere layer comprises:
[0041] Dissolving the polystyrene microspheres in an organic solvent, and removing the organic solvent after solidification and interface self-assembly reaction; and / or
[0042] The polystyrene microspheres have a concentration of 10-20% and are disposed on the interface of the hole functional layer, the curing comprises curing at 60-80° C. for 10-30 minutes, the interface self-assembly reaction time is 5-15 minutes, and the removal of the organic solvent comprises heating to 110-170° C.; and / or
[0043] The organic solvent includes one or more of toluene, dichloromethane, aromatic hydrocarbons, and halogenated hydrocarbons.
[0044] Optionally, in some embodiments of the present application, the method for removing the template etching layer includes an oxygen reactive etching method, and the oxygen reactive etching method includes:
[0045] At oxygen flow rate 10-30cm 3 / min and etching power 30-60W, etching for 6-15min.
[0046] The present application provides a display device, which includes the light-emitting device mentioned above; or, the display device includes the light-emitting device prepared by the above preparation method.
[0047] This application has the following beneficial effects:
[0048] The interface modification layer prepared in the present application can generate plasma excitation when irradiated with light through the raised structure of precious metal particles therein, generate a plasma hotspot at the tip apex, effectively enhance the electromagnetic field at the interface, and achieve a better carrier injection balance while promoting hole injection, thereby improving the brightness of the device. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] Figure 1 is a schematic diagram of the structure of an interface modification layer provided by an embodiment of the present invention;
[0050] Figure 2 is a flow chart of a method for preparing an interface modification layer provided by an embodiment of the present invention;
[0051] Figure 3 It is a schematic diagram of a template etching layer provided by an embodiment of the present invention;
[0052] Figure 4 is a schematic diagram of a metal nanocone array obtained according to an embodiment of the present invention;
[0053] Figure 5 is a schematic structural diagram of a light emitting device provided by an embodiment of the present invention;
[0054] Figure 6 It is a flow chart of a method for preparing a light-emitting device provided by an embodiment of the present invention.
[0055] Explanation of reference numerals: 100 - light-emitting device; 10 - first electrode, 20 - hole injection layer, 30 - hole transport layer, 40 - interface modification layer, 50 - light-emitting layer, 60 - electron transport layer, 70 - second electrode. DETAILED DESCRIPTION
[0056] The present invention will be further described below in conjunction with specific embodiments.
[0057] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without making creative work belong to the scope of protection of the present application. In addition, it should be understood that the specific implementation methods described herein are only used to illustrate and explain the present application, and are not used to limit the present application.
[0058] In this application, unless otherwise stated, directional words such as "upper" and "lower" generally refer to the upper and lower parts of the device in actual use or working state, specifically the drawing direction in the accompanying drawings; while "inner" and "outer" refer to the outline of the device. In addition, in the description of this application, the term "including" means "including but not limited to". The terms first, second, third, etc. are used only as labels and do not impose numerical requirements or establish an order.
[0059] In this application, "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural.
[0060] In the present application, "at least one" means one or more, and "plurality" means two or more. "At least one", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.
[0061] In the present application, when a layer is formed "on" another layer, the so-called "on" is a broad concept, which may indicate that the formed another layer is adjacent to the certain layer, or may indicate that there are other spacing structural layers between the another layer and the certain layer. For example, when a second electrode is formed "on" the first carrier functional layer, the so-called "on" may indicate that the formed second electrode is adjacent to the first carrier functional layer, or may indicate that there are other spacing structural layers between the second electrode and the first carrier functional layer, such as a light-emitting layer.
[0062] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.
[0063] In view of the problem that the size difference between the organic material and the quantum dots in the hole transport layer in the prior art is large, which makes it difficult to inject holes into the light-emitting layer, the present application provides a functional layer and an optical device. The technical solution of the present application is as follows:
[0064] First, please refer to the attached Figure 5 The embodiment of the present application provides a light-emitting device 100, including a substrate, a first electrode 10, a hole transport layer 30, an interface modification layer 40, a light-emitting layer 50, a second electrode 70 and an encapsulation layer stacked in sequence.
[0065] In some embodiments, the light emitting device 100 further includes a hole injection layer 20 disposed between the first electrode 10 and the hole transport layer 30 .
[0066] Furthermore, in some embodiments, the light emitting device 100 further includes an electron transport layer 60 disposed between the light emitting layer 50 and the second electrode 70 .
[0067] Please see attached Figure 1 The interface modification layer 40 includes an interface body and one or more metal protrusions disposed on the interface body. The interface modification layer 40 is located between the hole transport layer 30 and the light emitting layer 50, and the convex surface of the metal protrusion faces the light emitting layer 50.
[0068] In some embodiments, the materials of the interface body and the metal protrusion can be independently selected from but not limited to one or more of gold, silver, and platinum group metals, and the platinum group metals can include but are not limited to one or more of iridium, rhodium, palladium, and platinum.
[0069] The metal protrusion is arranged on the surface of the interface body close to the light-emitting layer 50 .
[0070] It is understandable that the interface body can be a single layer structure, or can be the bottom area of an array structure composed of a plurality of metal protrusions. For example, a plurality of the metal protrusions form an array to form a layered structure, namely the interface modification layer 40.
[0071] The metal protrusions include regular-shaped protrusions and irregular-shaped protrusions, and the regular-shaped protrusions include one or more of metal nano-conical protrusions, metal nano-hemispherical protrusions, metal nano-curved surface protrusions, metal nano-truncated cone protrusions, metal nano-wedge-shaped protrusions, and metal nano-polygonal protrusions.
[0072] It should be noted that, in the present embodiment, the irregular shaped protrusion refers to the irregular shape of the protrusion, that is, its shape is not a standard three-dimensional shape, such as a regular shape such as a sphere, a cube, a cylinder, a cone, a prism, a regular tetrahedron, etc. For example, the irregular shaped protrusion can be understood as a structure in which the bottom size of the protrusion is larger than the top size in the direction from the interface body to the light-emitting layer. In addition, a plurality of irregular shaped protrusions can be arranged in a regular pattern on the interface modification layer (i.e., the shapes of the plurality of protrusions are consistent, the arrangement direction is consistent, and the spacing between them is consistent), or they can be arranged in an irregular and chaotic manner.
[0073] The light emitting device further includes an electron transport layer disposed between the light emitting layer and the second electrode.
[0074] The diameter of the luminescent nanoparticles in the luminescent layer is 5-10 nm. For example, the diameter of the luminescent nanoparticles can be 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, 10 nm, and a value within the range between any two of the above-listed values. Within the diameter range of the luminescent nanoparticles, it is more conducive to transition through the pointed cone structure of the metal nanocone array, which can reduce the difference in morphology and size between the two, thereby reducing the difference in transmission between the two-dimensional material interface and the three-dimensional material interface.
[0075] In some embodiments, the average height of the metal protrusion is 10-20 nm. For example, the average height of the metal protrusion can be 10 nm, 11 nm, 12 nm, 15 nm, 17 nm, 19 nm, 20 nm, and values within a range between any two of the above values. Within the height range, the metal protrusion is conducive to forming a tip that is more conducive to generating plasmons.
[0076] The average spacing between the tops of two adjacent metal protrusions is 20-300 nm. For example, the average spacing between the tops of two adjacent metal protrusions can be 20 nm, 50 nm, 75 nm, 100 nm, 150 nm, 200 nm, 240 nm, 300 nm, and any value between any two of the above values. Within the range of the tapered tip spacing, it is beneficial to improve the hole transport efficiency.
[0077] The average diameter or average equivalent diameter of the metal protrusion near the interface body is 5-10nm. For example, the average diameter or equivalent diameter of the bottom of the metal nanoprotrusion can be 5nm, 6nm, 7nm, 8nm, 9nm, 10nm, and values within the range between any two of the above values.
[0078] The average diameter or average equivalent diameter of the metal protrusion in the projected area on the interface body is 5-10 nm.
[0079] The metal nano-cone-shaped protrusions include metal nano-cone-shaped protrusions and metal nano-pyramid-shaped protrusions, and the metal nano-hemispherical protrusions also include metal nano-semi-ellipsoidal protrusions.
[0080] The interface modification layer prepared in the present application, for example, uses a metal nanocone array structure as an interface modification layer, utilizes the plasma exciton characteristics of the noble metal surface, increases the electric field intensity, generates ion heat, and increases the injection of holes through a pointed cone structure, promotes the transmission of hole carriers, improves the coupled light output of the device, and thus improves the brightness of the device and the hole transmission efficiency; on the other hand, the material of the hole functional layer is the interface of a sheet-like two-dimensional material, and the light-emitting layer is the interface of a granular quantum dot material. There are difficulties in the hole transmission process from the interface of the two-dimensional material to the interface of the three-dimensional material. By transitioning through a metal protrusion, such as a pointed cone structure of a metal nanocone array, the difference in morphology and size between the two can be reduced, thereby reducing the difference in transmission between the interface of the two-dimensional material and the interface of the three-dimensional material. Therefore, the metal protrusion, i.e., the pointed cone structure of the metal nanocone, needs to face the light-emitting layer, that is, the metal nanocone array is prepared at the interface of the hole transmission layer. The array structure composed of the metal protrusions is located between the hole transmission layer and the light-emitting layer because the plasma exciton effect can only produce an effect at the interface of the hole transmission layer, and no plasma excitons can be produced in other layers.
[0081] In some embodiments, the thickness of the hole transport layer is 20-50nm; the diameter of the luminescent nanoparticles in the luminescent layer is 5-10nm, and the bottom diameter of the metal nanocones in the metal nanocone array in the interface modification layer is 5-10nm. As an example, the thickness of the hole transport layer is 20nm, 30nm, 40nm, and 50nm; the diameter of the luminescent nanoparticles in the luminescent layer is 5nm, 8nm, and 10nm. Within the thickness range of the hole transport layer, it is more conducive to improving the hole transport efficiency. Within the diameter range of the luminescent nanoparticles, it is more conducive to transition through the pointed cone structure of the metal nanocone array, which can make up for the difference in morphology and size between the two, thereby reducing the difference in transmission between the two-dimensional material interface and the three-dimensional material interface.
[0082] In some embodiments, the hole transport layer includes alternating stacks of nanosheets of different types.
[0083] The different types of nanosheets include nanosheets of different thicknesses and / or nanosheets of different materials.
[0084] The material of the nanosheet includes a two-dimensional material, and the two-dimensional material includes one of graphene, boron nitride, molybdenum disulfide, carbon nanotubes, fullerenes, carbon nanosheets, tungsten disulfide, molybdenum diselenide, tungsten diselenide, and MXene.
[0085] The thickness of the nanosheet is 3-4 nm. For example, the thickness of the nanosheet can be 3.2 nm, 3.4 nm, 3.6 nm, 3.8 nm, 4.0 nm, and values within the range between any two of the above values.
[0086] In some embodiments, the hole transport layer is composed of two different types of nanosheets alternately stacked. For example, the hole transport layer can be composed of two nanosheets of different thicknesses alternately stacked, or it can be composed of two nanosheets of different materials alternately stacked. For example, a composite material obtained by alternately stacking graphene nanosheets and BN nanosheets for several times, a composite material obtained by alternately stacking MoS2 nanosheets and BN nanosheets for several times, a composite material obtained by alternately stacking carbon nanotube nanosheets and fullerene nanosheets for several times, and a composite material obtained by alternately stacking carbon nanosheets and C60 nanosheets for several times.
[0087] In some embodiments, the materials of the first electrode and the second electrode may be materials known in the art for electrodes, independently including but not limited to one or more of metals, carbon materials and metal oxides, the metals including one or more of Al, Ag, Cu, Mo, Au, Ba, Ca, Yb and Mg; the carbon materials including one or more of graphite, carbon nanotubes, graphene and carbon fibers; the metal oxides including doped or undoped metal oxides including one or more of ITO, FTO, ATO, AZO, GZO, IZO, MZO and AMO, or including a composite electrode in which a metal is sandwiched between doped or undoped transparent metal oxides, the composite electrode including one or more of AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, ZnS / Ag / ZnS, ZnS / Al / ZnS, TiO2 / Ag / TiO2 and TiO2 / Al / TiO2.
[0088] The material of the hole injection layer can be a material known in the art for the hole injection layer, for example, it can be selected from but not limited to 2,3,6,7,10,11-hexacyano-1,4,5,8,9,12-hexaazatriphenylene (HAT-CN), PEDOT, PEDOT:PSS, a derivative of PEDOT:PSS doped with s-MoO3 (PEDOT:PSS:s-MoO3), 4,4',4'-tris(N-3-methylphenyl-N-phenylamino)triphenylamine (m-MTDATA), tetracyanoquinodimethane (F4-TCQN), copper phthalocyanine, nickel oxide, molybdenum oxide, tungsten oxide, vanadium oxide, molybdenum sulfide, tungsten sulfide and copper oxide. One or more.
[0089] The material of the light-emitting layer may include but is not limited to one or more of quantum dot light-emitting materials, that is, the quantum dot light-emitting materials in the quantum dot layer may include but are not limited to one or more of single structure quantum dots, core-shell structure quantum dots and perovskite semiconductor materials.
[0090] The material of the single structure quantum dots, the core material of the core-shell structure quantum dots and the shell material of the core-shell structure quantum dots may respectively include but are not limited to one or more of II-VI group compounds, IV-VI group compounds, III-V group compounds and I-III-VI group compounds. The II-VI group compounds may include, but are not limited to, one or more of CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe. The IV-VI group compounds may include, but are not limited to, one or more of SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe, and SnPbSTe. The III-V group compound may include, but is not limited to, one or more of GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs, and InAlPSb. The I-III-VI group compound may include, but is not limited to, one or more of CuInS2, CuInSe2, and AgInS2.
[0091] As an example, the core-shell structured quantum dots may include, but are not limited to, one or more of CdSe / CdSeS / CdS, InP / ZnSeS / ZnS, CdZnSe / ZnSe / ZnS, CdSeS / ZnSeS / ZnS, CdSe / ZnS, CdSe / ZnSe / ZnS, ZnSe / ZnS, ZnSeTe / ZnS, CdSe / CdZnSeS / ZnS and InP / ZnSe / ZnS.
[0092] The material of the electron transport layer is a material known in the art for the electron transport layer, including but not limited to one or more of inorganic electron transport materials and organic electron transport materials. The inorganic electron transport material includes one or more of doped or undoped zinc oxide, barium oxide, titanium oxide, tin oxide, tantalum oxide, zirconium oxide, cadmium sulfide, zinc sulfide, zinc tin, indium phosphide, gallium phosphide, and barium titanate, wherein the doped element includes one or more of aluminum, magnesium, lithium, manganese, yttrium, lanthanum, copper, nickel, zirconium, cerium, and gadolinium. The organic electron transport material includes one or more of quinoxaline compounds, imidazole compounds, triazine compounds, fluorene-containing compounds, and hydroxyquinoline compounds.
[0093] It is understandable that the light-emitting device may also be provided with some functional layers conventionally used in light-emitting devices to help improve the performance of the light-emitting device, such as an electron blocking layer, a hole blocking layer, etc.
[0094] It can be understood that the materials of each layer of the light-emitting device can be adjusted according to the light-emitting requirements of the light-emitting device.
[0095] It can be understood that the light-emitting device can be a positive light-emitting device or an inverted light-emitting device, and the light-emitting device can be a quantum dot light-emitting device or an organic light-emitting device, that is, the first electrode is an anode and the second electrode is a cathode; or, the first electrode is a cathode and the second electrode is an anode. For example: the inverted light-emitting device structure is set to be anode / electron transport layer / light-emitting layer / interface modification layer / hole transport layer of two-dimensional material / hole injection layer / cathode.
[0096] The hole transport layer prepared by stacking two different two-dimensional materials in the present application has better stability than the existing technology. The two-dimensional layered material has good thermal transport properties and can promote hole injection; however, the two-dimensional material is in sheet form and has a large size difference with the quantum dot nanoparticles, which is not conducive to hole injection. Therefore, in addition to using metal nanocone arrays to reduce the morphological difference between the two, the diameter of the luminescent nanoparticles in the luminescent layer and the diameter of the bottom surface of the metal nanocones in the metal nanocone array in the interface modification layer are also set to 5-10nm, thereby further reducing the difficulty of hole transport and solving the problem of poor hole transport effect.
[0097] For the second aspect, please refer to the attached Figure 6 The present invention provides a method for preparing a light-emitting device, comprising the following steps:
[0098] S11, providing a first electrode;
[0099] S12, forming a hole functional layer on the first electrode;
[0100] S13, forming the interface modification layer in the light-emitting device as described above on the hole functional layer;
[0101] S14, forming a light-emitting layer on the interface modification layer; S15, forming a second electrode on the light-emitting layer to obtain a light-emitting device.
[0102] In some embodiments, the hole functional layer includes a hole transport layer and / or a hole injection layer.
[0103] When the hole functional layer includes a hole transport layer and / or a hole injection layer, the hole transport layer or the hole injection layer is arranged between the first electrode and the interface modification layer.
[0104] When the hole functional layer includes a hole transport layer and a hole injection layer, the hole injection layer is disposed between the first electrode and the interface modification layer, and the hole transport layer is disposed between the hole injection layer and the interface modification layer.
[0105] The metal protrusions include one or more of metal nanocones and metal nanospheres having conical tips.
[0106] The interface modification layer comprises an interface body and a metal protrusion, wherein the convex surface of the metal protrusion faces the light-emitting layer.
[0107] An electronic functional layer is further provided between the light-emitting layer and the second electrode, and the electronic functional layer includes an electron transport layer.
[0108] In some embodiments, the first electrode is made of a magnetron sputtered ITO film.
[0109] The hole injection layer preparation method includes printing or spin coating, and the thickness is 30-40nm; for example: 30nm, 35nm, 40nm; within the thickness range of the hole injection layer, it is more conducive to improving the hole transmission efficiency.
[0110] The method of setting the hole transport layer of the two-dimensional material on the hole injection layer includes adopting a transfer method, first preparing the hole transport layer on PMMA, and then transferring it to the hole injection layer; specifically, coating the two-dimensional material on PMMA, heating at 60-200° C. for 5-30 minutes to obtain a two-dimensional material film set on the surface of PMMA, and then covering the two-dimensional material film on the hole injection layer, and then soaking it in 20-80° C. acetone for 5-15 minutes to remove the PMMA on the surface;
[0111] The hole transport layer thickness of the two-dimensional material is 20-50 nm, for example 20 nm, 30 nm, 40 nm, 50 nm. Within the thickness range of the hole transport layer, it is more conducive to improving the hole transport efficiency.
[0112] In step S13:
[0113] Please see attached Figure 2 , the preparation method of the interface modification layer of this application, please refer to the attached Figure 3-4 The present application adopts a method of microsphere self-assembly, so that after the microspheres self-assemble into a single layer, during the process of evaporating the metal nanocone array, the metal nanocone array is plated on the surface of the microsphere particles and filled in the gap between the microsphere particles and the etching layer. The microspheres can be removed by oxygen reaction etching. When removing the microspheres, only the metal nanocone array on the surface of the microspheres is removed, and the metal nanoparticles in the gap between the microsphere particles are left, thereby forming a metal nanocone array. Specifically, the following steps are included:
[0114] S21, setting a template etching layer;
[0115] S22, using the template etching layer as a template to set a metal protrusion;
[0116] S23, removing the template etching layer to obtain a plurality of metal protrusions, namely, an interface modification layer.
[0117] In step S21:
[0118] The template etching layer is arranged on the hole functional layer, and includes a self-assembled microsphere layer, and the microsphere layer includes materials such as polystyrene (PS), silicon dioxide, etc.; the method for preparing PS microspheres includes a self-assembly method, that is, the microspheres are spread on the interface of the hole functional layer, and due to the diffusion of water and surface tension, the microspheres form a single-layer structure, and due to the strong interaction between the microspheres, an orderly arrangement is formed, specifically: polystyrene (PS) microspheres with a diameter of 20-300nm and a concentration of 10-20% are dissolved in an organic solvent, and then arranged on the hole functional layer, cured at 60-80°C for 10-30min, and subjected to an interface self-assembly reaction for 5-15min to assemble a layer of PS microspheres. The PS microspheres are then heated to 110-170°C to remove the organic solvent, thereby obtaining self-assembled PS microspheres; the PS microspheres have a diameter of 0.02-0.3 microns; as an example, the diameter of the polystyrene microspheres is 20nm, 50nm, 100nm, 150nm, 200nm, 240nm, 280nm, 300nm or a value between any two of the above values, and the concentration is 10%, 14%, 18%, 20% or a value between any two of the above values; the curing temperature is 60°C, 70°C, 80°C; the heating temperature when removing the microspheres is 110°C, 130°C, 150°C, 170°C or a value between any two of the above values. Within the range of the microsphere concentration, curing temperature, heating temperature, and self-assembly reaction time, it is more conducive to the formation of the template etching layer and the uniform dispersion and arrangement of the microspheres.
[0119] The organic solvent includes one or more of toluene, dichloromethane, aromatic hydrocarbons, and halogenated hydrocarbons.
[0120] The interface modification layer comprises at least one array of the metal protrusions, and the metal protrusions comprise metal nanocones and metal nanospheres with conical tips.
[0121] In step S22:
[0122] The method for preparing the metal protrusion array includes a vacuum evaporation method.
[0123] The material used for the metal protrusions includes precious metals such as gold, silver, and platinum group metals that can generate plasmons;
[0124] The platinum group metal includes one of iridium, rhodium, palladium and platinum.
[0125] In step S23:
[0126] The method for removing the template etching layer includes a method of using oxygen reaction etching, and the method of oxygen reaction etching includes the following steps:
[0127] At oxygen flow rate 10-30cm 3 / min, etching power 30-60W, etching 6-15min.
[0128] As an example, the oxygen flow rate is 10cm 3 / min、15cm 3 / min、20cm 3 / min、25cm 3 / min、30cm 3 / min; etching power is 30W, 40W, 50W, 60W; etching time can be 6min, 9min, 12min, 15min. Within the range of oxygen flow rate, etching power and etching time, it is more conducive to the removal of the template etching layer.
[0129] The thickness of the light-emitting layer is 30-60 nm, for example, 30 nm, 40 nm, 50 nm, and 60 nm. Within the thickness range of the light-emitting layer, it is more conducive to improving the brightness of the device.
[0130] The method for preparing the light-emitting layer includes printing or spin coating;
[0131] The thickness of the electron transport layer is 30-30 nm, for example, 30 nm, 50 nm, 70 nm, 90 nm, 110 nm, 130 nm, 150 nm. Within the thickness range of the electron transport layer, it is more conducive to improving the electron transport efficiency.
[0132] The electron transport preparation method includes printing or spin coating.
[0133] When the second electrode is a cathode, the electrode evaporation thickness is 50-100nm, and the evaporation speed is 0.1-0.3nm / s. As an example, the electrode evaporation thickness is 50nm, 80nm, 100nm, and the evaporation speed is 0.1nm / s, 0.2nm / s, 0.3nm / s; within the evaporation thickness and speed range, it is more conducive to preparing the above electrode.
[0134] The present application optimizes the structure and materials of the light-emitting device and utilizes the small size difference between the hole transport layer material and the QD material to promote the rapid transport and injection of holes, so that the device achieves carrier balance, and is beneficial to the good stability and thermal transport properties of the hole transport layer material, promotes the injection of thermal excitons into the QD layer, and reduces the turn-on voltage of the device. In addition, the precious metal nano-tip cone array in the interface modification layer can better couple light. The increase of multiple factors not only improves the device efficiency and brightness, but also improves the device life.
[0135] The embodiments of the present application also provide materials for the above-mentioned hole transport layer, including composite materials obtained by alternately stacking two two-dimensional materials for several times; the two-dimensional materials include graphene nanosheets, boron nitride (BN) nanosheets, MoS2 nanosheets, carbon nanotubes, fullerene nanosheets, carbon nanosheets, tungsten disulfide (WS2), molybdenum diselenide (MoSe2), tungsten diselenide (WSe2), MXene; for example, a composite material obtained by alternately stacking graphene nanosheets and BN nanosheets for several times, a composite material obtained by alternately stacking MoS2 nanosheets and BN nanosheets for several times, a composite material obtained by alternately stacking carbon nanotube nanosheets and fullerene nanosheets for several times, and a composite material obtained by alternately stacking carbon nanosheets and C60 nanosheets for several times;
[0136] The present application also provides a method for preparing the hole transport layer material, comprising the following steps:
[0137] S31, plating a first nanosheet on a substrate under a gas atmosphere;
[0138] S32, then plating a second nanosheet in a BCl3, hydrogen, and nitrogen atmosphere;
[0139] S33, alternately repeating steps S11 and S12 until the thickness reaches 20-50 nm;
[0140] In step S31:
[0141] Before plating the first nanosheet, the substrate is cleaned and the air is exhausted to a vacuum degree of 2×10 -5 -3×10 - 4 Pa;
[0142] The method for plating the first nanosheet includes using a plasma chemical vapor deposition (PECVD) method or an evaporation method; the chemical vapor deposition method includes: heating to 500-800°C under a gas atmosphere, a radio frequency power of 110-160W, and growing for 30-50min; the gas atmosphere includes a gas containing the same element as the first nanosheet material, for example, a gas containing a B source and a N source is selected for plating BN nanosheets, molybdenum vapor and sulfur vapor are selected for plating molybdenum disulfide nanosheets, and methane and hydrogen are selected for plating graphene nanosheets; for example: temperature 500°C, 600°C, 700°C, 800°C, radio frequency power 110W, 120W, 130W, 140W, 150W, 160W, time 30min, 40min, 50min; within the temperature and radio frequency power range, it is conducive to plating the above-mentioned first nanosheet.
[0143] The thickness of each layer of the first nanosheet includes 3-4 nm, for example, 3 nm, 3.2 nm, 3.4 nm, 3.6 nm, 3.8 nm, and 4 nm. Within the thickness range of the first nanosheet, it is beneficial to improve the hole transport efficiency.
[0144] When plating the first nanosheet, copper foil is used as a substrate, and the substrate also includes a silicon wafer substrate.
[0145] In step S32:
[0146] The method for plating the second nanosheet includes a PECVD method and an evaporation method; the PECVD method includes: at room temperature, the gas flow ratio of BCl3, hydrogen and nitrogen atmosphere is 1:1:(5-10), the radio frequency power is 130-150W, and the reaction time is 40-50min; for example: the radio frequency power is 130W, 140W, 150W, and the reaction time is 40min, 45min, 50min; within the range of the atmosphere flow ratio, temperature, and radio frequency power, it is conducive to plating the above-mentioned second nanosheet.
[0147] The thickness of each layer of the plated second nanosheet is 3-3.5 nm, for example, 3 nm, 3.3 nm, and 3.5 nm. Within the thickness range of the second nanosheet, it is beneficial to improve the hole transport efficiency.
[0148] The substrate may be a rigid substrate or a flexible substrate. In some embodiments, the material of the substrate may include but is not limited to one or more of glass, silicon wafer, polycarbonate, polymethyl methacrylate, polyethylene terephthalate, polyethylene naphthalate, polyamide and polyether sulfone.
[0149] This application uses two two-dimensional materials with interlayer van der Waals effects to form a hole transport layer, which reduces the size difference between the hole transport material and the quantum dot size, promotes hole injection, and at the same time, the two-dimensional materials are alternately stacked as the hole transport layer, which has good stability and heat transport performance, so that the device's turn-on voltage is reduced, has high carrier mobility, and improves the efficiency and life of the device. However, when more two-dimensional materials (for example, three or more two-dimensional materials) are alternately stacked as the hole transport layer, due to the large differences in the materials, the thermal matching of the materials will be poor when heated.
[0150] In a third aspect, the present application also provides a display device, which includes the above-mentioned light-emitting device.
[0151] The display device can be any electronic product with a display function, including but not limited to smart phones, tablet computers, laptops, digital cameras, digital video cameras, smart wearable devices, smart weighing electronic scales, car displays, televisions or e-book readers, among which smart wearable devices can be, for example, smart bracelets, smart watches, virtual reality (VR) helmets, etc.
[0152] Example 1
[0153] The present embodiment provides a light-emitting device, including a substrate, a QLED electronic component bonded to the substrate, and an encapsulation film for encapsulating the QLED electronic component. The structure of the light-emitting device is: an ITO bottom electrode, a PEDOT hole injection layer with a thickness of 40nm, a two-dimensional graphene / boron nitride composite hole transport layer with a thickness of 20nm, a silver tip nanocone interface modification layer with a thickness of 10nm and a bottom diameter of 5nm, a red quantum dot light-emitting layer with a thickness of 20nm, a ZnO electron transport layer with a thickness of 30nm, a silver top electrode with a thickness of 70nm, and a cover plate package.
[0154] The light emitting device of this embodiment is prepared according to the following method:
[0155] A hole injection layer is prepared on the ITO bottom electrode. The material is PEDOT with a thickness of about 40 nm.
[0156] The PECVD method is used to prepare a two-dimensional graphene / boron nitride composite nanosheet material film, and the preparation method is as follows:
[0157] Use copper foil as substrate, clean it and put it into the PECVD reaction chamber, evacuate it and wait until the vacuum reaches 3×10 -4 After Pa, in an atmosphere of 30sccm methane and 20sccm hydrogen, it was heated to 500°C, the RF power was turned on with a power of 110W, and the growth was carried out for 30min to obtain a layer of graphene nanosheet (3.5nm), and the power was turned off to wait for the sample to cool to room temperature; then in the reaction chamber, in an atmosphere of 5sccm BCl3, 5sccm hydrogen and 40sccm nitrogen, the RF power was turned on with a power of 130W, and the reaction was carried out for 40min to obtain a layer of BN (3nm) nanosheet, and the alternating covering was repeated 3 times to obtain a graphene / BN composite material with a thickness of 20nm.
[0158] A graphene / BN composite material of corresponding thickness is obtained, and then PMMA material is coated on its surface, heated at 60°C for 5 minutes, and the composite film is glassed on the PMMA surface to obtain a PMMA surface film; then the PMMA surface film is covered on PEDOT, and acetone is used to remove PMMA to obtain a PEDOT / graphene / BN composite film.
[0159] Preparation of interface modification layer:
[0160] 10% polystyrene (PS) microspheres with a diameter of 300 nm were dissolved in a toluene solution and then spin-coated on a graphene / BN composite film. The microspheres were cured at 60°C for 10 min, and then subjected to an interface self-assembly reaction for 5 min to assemble a layer of PS microspheres. The toluene solution was removed at 110°C to obtain self-assembled PS microspheres. 10 nm of Ag was evaporated on the PS microspheres, and the PS microspheres were removed by oxygen reactive etching to obtain an interface modification layer containing a silver particle array with a pointed cone and a spacing of approximately 300 nm.
[0161] A red QD functional layer and a zinc oxide functional layer are sequentially formed on the interface modification layer according to the QLED structure of this embodiment.
[0162] Then, a silver electrode with a thickness of 70 nm was prepared by silver evaporation method, and a cover plate was used for packaging.
[0163] Example 2
[0164] The present embodiment provides a light-emitting device, which includes a substrate, a QLED electronic component bonded to the substrate, and an encapsulation film for encapsulating the QLED electronic component. The structure of the light-emitting device is: an ITO bottom electrode, a PEDOT hole injection layer with a thickness of 40nm, a two-dimensional graphene / boron nitride composite hole transport layer with a thickness of 20nm, a silver tip nanocone interface modification layer with a thickness of 10nm, a blue quantum dot light-emitting layer with a thickness of 20nm, a ZnO electron transport layer with a thickness of 30nm, a silver top electrode with a thickness of 70nm, and a cover plate package.
[0165] The light emitting device of this embodiment is prepared according to the following method:
[0166] A hole injection layer was prepared on the ITO bottom electrode, the material was PEDOT, and the thickness was 40 nm;
[0167] The two-dimensional graphene / boron nitride composite nanosheet material film is prepared by PECVD method, and the preparation method is as follows:
[0168] Use copper foil as substrate, clean it and put it into the PECVD reaction chamber, evacuate it and wait until the vacuum reaches 3×10 -4After Pa, in an atmosphere of 30sccm methane and 20sccm hydrogen, it was heated to 500°C, the RF power was turned on with a power of 110W, and the growth was carried out for 30min to obtain a layer of graphene nanosheet (3.5nm), and the power was turned off to wait for the sample to cool to room temperature; then in the reaction chamber, in an atmosphere of 5sccm BCl3, 5sccm hydrogen and 40sccm nitrogen, the RF power was turned on with a power of 130W, and the reaction was carried out for 40min to obtain a layer of BN (3nm) nanosheet, and the alternating covering was repeated 8 times to obtain a graphene / BN composite material with a thickness of 50nm.
[0169] A graphene / BN composite material of corresponding thickness is obtained and then PMMA material is coated on its surface, heated at 60°C for 5 minutes, the composite film is glassed on the PMMA surface, and then the PMMA surface film is covered on PEDOT, and PMMA is removed by acetone to obtain a PEDOT / graphene / BN composite film.
[0170] Preparation of interface modification layer:
[0171] 10% polystyrene (PS) microspheres with a diameter of 300 nm were dissolved in a toluene solution and then spin-coated onto a graphene / BN composite film. The microspheres were cured at 60°C for 10 min, and then subjected to an interface self-assembly reaction for 5 min to assemble a layer of PS microspheres. The toluene solution was then removed at 110°C to obtain self-assembled PS microspheres. 10 nm of Ag was evaporated on the PS microspheres, and then the PS microspheres were removed by oxygen reactive etching to obtain an interface modification layer containing a silver particle array with a pointed cone and a spacing of approximately 300 nm.
[0172] A blue QD functional layer and a zinc oxide functional layer are sequentially formed on the interface modification layer substrate according to the QLED structure of this embodiment.
[0173] Then, a silver electrode with a thickness of 70 nm was prepared by silver evaporation method, and a cover plate was used for packaging.
[0174] Example 3
[0175] This embodiment provides a light-emitting device, including a substrate, a QLED electronic component bonded to the substrate, and an encapsulation film for encapsulating the QLED electronic component. The structure of the light-emitting device is: an ITO bottom electrode, a PEDOT hole injection layer with a thickness of 40nm, a two-dimensional graphene / boron nitride composite hole transport layer with a thickness of 20nm, a silver tip nanocone interface modification layer with a thickness of 20nm, a red quantum dot light-emitting layer with a thickness of 20nm, a ZnO electron transport layer with a thickness of 30nm, a silver top electrode with a thickness of 70nm, and a cover plate package.
[0176] The light emitting device of this embodiment is prepared according to the following method:
[0177] A hole injection layer was prepared on the ITO bottom electrode, the material was PEDOT, and the thickness was 40 nm;
[0178] The PECVD method is used to prepare a two-dimensional graphene / boron nitride composite nanosheet material film, and the preparation method is as follows:
[0179] Use copper foil as substrate, clean it and put it into the PECVD reaction chamber, evacuate it and wait until the vacuum reaches 3×10 -4 After Pa, in an atmosphere of 30sccm methane and 20sccm hydrogen, it was heated to 500°C, the RF power was turned on with a power of 110W, and the growth was carried out for 30min to obtain a layer of graphene nanosheet (3.5nm), and then the power was turned off and the sample was cooled to room temperature; then in the reaction chamber, in an atmosphere of 5sccm BCl3, 5sccm hydrogen and 40sccm nitrogen, the RF power was turned on with a power of 130W, and the reaction was carried out for 40min to obtain a layer of BN (3nm) nanosheet, and the alternating covering was repeated 3 times to obtain a graphene / BN composite material with a thickness of 20nm.
[0180] A graphene / BN composite material of corresponding thickness is obtained and then PMMA material is coated on its surface, heated at 60°C for 5 minutes, the composite film is glassed on the PMMA surface, and then the PMMA surface film is covered on PEDOT, and PMMA is removed by acetone to obtain a PEDOT / graphene / BN composite film.
[0181] Preparation of interface modification layer:
[0182] 10% polystyrene (PS) microspheres with a diameter of 300 nm were dissolved in a toluene solution and then spin-coated on a graphene / BN composite film. The solution was cured at 60°C for 10 min, and then the interface self-assembly reaction was performed for 5 min to assemble a layer of PS microspheres. The toluene solution was then removed at 110°C to obtain self-assembled PS microspheres. 20 nm of Ag was evaporated on the PS microspheres, and then the PS microspheres were removed by oxygen reactive etching to obtain an interface modification layer containing a silver particle array with a pointed cone and a spacing of about 300 nm.
[0183] A red QD functional layer and a zinc oxide functional layer are sequentially formed on the substrate of the interface modification layer according to the QLED structure of this embodiment.
[0184] Then, a silver electrode with a thickness of 70 nm was prepared by silver evaporation method, and a cover plate was used for packaging.
[0185] Example 4
[0186] The present embodiment provides a light-emitting device, including a substrate, a QLED electronic component bonded to the substrate, and an encapsulation film for encapsulating the QLED electronic component. The structure of the light-emitting device is: an ITO bottom electrode, a PEDOT hole injection layer with a thickness of 40nm, a two-dimensional MoS2 / boron nitride composite hole transport layer with a thickness of 20nm, a silver tip nanocone interface modification layer with a thickness of 10nm, a red quantum dot light-emitting layer with a thickness of 20nm, a ZnO electron transport layer with a thickness of 30nm, a silver top electrode with a thickness of 70nm, and a cover plate package.
[0187] The light emitting device of this embodiment is prepared according to the following method:
[0188] A hole injection layer was prepared on the ITO bottom electrode, the material was PEDOT, and the thickness was 40 nm;
[0189] The PECVD method is used to prepare a two-dimensional molybdenum disulfide / boron nitride composite nanosheet material film, and the preparation method is as follows:
[0190] Use copper foil as substrate, clean it and put it into the PECVD reaction chamber, evacuate it and wait until the vacuum reaches 3×10 -4 After Pa, 25sccm molybdenum oxide vapor and 50sccm sulfur vapor were introduced, heated to 600℃, the RF power was turned on at 120W, and the growth was carried out for 40min to obtain a layer of molybdenum disulfide nanosheets (3.2nm), and then the power was turned off and the sample was cooled to room temperature; then in the reaction chamber, 5sccm BCl3 atmosphere, 5sccm hydrogen atmosphere and 40sccm nitrogen atmosphere were introduced, the RF power was turned on at 130W, and the reaction was carried out for 40min to obtain a layer of BN (3nm) nanosheets, and the alternating coverage was repeated 3 times to obtain a molybdenum disulfide / BN composite material with a thickness of 20nm. Among them, the reaction rate is slow when the nitrogen flow rate is low, and the reaction rate is fast when the nitrogen flow rate is fast.
[0191] A graphene / BN composite material of corresponding thickness is obtained and then PMMA material is coated on its surface, heated at 60°C for 5 minutes, the composite film glass is placed on the PMMA surface, and then the PMMA surface film is covered on PEDOT, and PMMA is removed by acetone to obtain a PEDOT / molybdenum disulfide / BN composite film.
[0192] Preparation of interface modification layer:
[0193] 10% polystyrene (PS) microspheres with a diameter of 300 nm were dissolved in a toluene solution and then spin-coated onto a graphene / BN composite film. The microspheres were cured at 60°C for 10 min, and then subjected to an interface self-assembly reaction for 5 min to assemble a layer of PS microspheres. The toluene solution was then removed at 110°C to obtain self-assembled PS microspheres. 10 nm of Ag was evaporated on the PS microspheres, and then the PS microspheres were removed by oxygen reactive etching to obtain an interface modification layer containing a silver particle array with a pointed cone and a spacing of approximately 300 nm.
[0194] A red QD functional layer and a zinc oxide functional layer are sequentially formed on the interface modification layer according to the QLED structure of this embodiment.
[0195] Then, a silver electrode with a thickness of 70 nm was prepared by silver evaporation method, and a cover plate was used for packaging.
[0196] Example 5
[0197] This embodiment is substantially the same as Embodiment 1, except that the thickness of the two-dimensional graphene / boron nitride composite material in this embodiment is 30 nm.
[0198] Example 6
[0199] This embodiment is basically the same as Embodiment 1, except that in this embodiment, the bottom diameter of the silver tip is 8 nm and the height is 10 nm.
[0200] Example 7
[0201] This embodiment is basically the same as Embodiment 1, except that, in this embodiment, the bottom surface diameter of the silver tip is 10 nm and the height is 10 nm.
[0202] Example 8
[0203] This embodiment is basically the same as Embodiment 1, except that, in this embodiment, the thickness of the silver tip nanocone is 14 nm.
[0204] Example 9
[0205] This embodiment is basically the same as Embodiment 1, except that the metal material used for the interface modification layer in this embodiment is gold.
[0206] Example 10
[0207] This embodiment is basically the same as Embodiment 1, except that the distance between the metal array particles in the interface modification layer in this embodiment is 200 nm.
[0208] Embodiment 11
[0209] This embodiment is basically the same as Embodiment 1, except that the distance between the metal array particles in the interface modification layer in this embodiment is 260 nm.
[0210] Example 12
[0211] This embodiment is substantially the same as Embodiment 1, except that the thickness of the two-dimensional graphene / boron nitride composite material in this embodiment is 50 nm.
[0212] Embodiment 13
[0213] This embodiment is substantially the same as the embodiment 1, except that the metal nanocone array of the interface modification layer in this embodiment is in the shape of a metal nanosphere array with a diameter of 6 nm.
[0214] Comparative Example 1
[0215] This comparative example is substantially the same as Example 1, except that in this comparative example, 20 nm thick TFB is used as the material of the hole transport layer.
[0216] Comparative Example 2
[0217] This comparative example is substantially the same as Example 1, except that no interface modification layer of the silver tip nanocone array is provided in this comparative example.
[0218] Comparative Example 3
[0219] This comparative example is substantially the same as Example 1, except that in this comparative example, the thickness of the TFB / PVK composite material is 20 nm.
[0220] Comparative Example 4
[0221] This embodiment is basically the same as Embodiment 1, except that the material used for the interface modification layer in this embodiment is copper.
[0222] Comparative Example 5
[0223] This comparative example is substantially the same as Example 2, except that in this comparative example, 20 nm thick TFB is used as the material of the hole transport layer.
[0224] Comparative Example 6
[0225] This comparative example is substantially the same as Example 2, except that no interface modification layer of the silver tip nanocone array is provided in this comparative example.
[0226] The EQE, lifespan T95@1000nit, and start-up voltage of Examples 1-13 and Comparative Examples 1-6 were tested for performance. The test results are shown in Table 1.
[0227] The test method for life span T95@1000nit is: in CDA gas, under constant current or voltage drive, measure the time taken for the device brightness to decay to a certain proportion of the maximum brightness, and the time taken for the brightness to decay to 95% of the maximum brightness is defined as T95, and this life span is the measured life span. In order to shorten the life span test cycle, the device life span test is usually carried out at high brightness by accelerating device aging, and the life span at low brightness is obtained by fitting the decay fitting formula. For example, the life span at 1000nits is recorded as T95@1000nits, and the calculation formula is:
[0228]
[0229] Among them, T95 L The lifespan under low brightness, generally 1000nits, T95 H is the lifespan under high brightness, that is, the measured lifespan, L H is the maximum brightness that the device is accelerated to, L L Generally, it is 1000nits, A is the acceleration factor, which is 1.7. The constant current is 2mA.
[0230] The test method for external quantum efficiency EQE is: using FPD optical property measurement equipment from Foster, controlling the efficiency test system built by QE PRO spectrometer, Keithley 2400, and Keithley 6485 through LabView, measuring parameters such as voltage, current, brightness, and luminescence spectrum, and calculating the external quantum efficiency EQE of the device.
[0231] Thermal transport performance test method: The 3ω method is used to test the thermal conductivity of the material.
[0232] The test results are: the thermal conductivity of the graphene / BN two-dimensional composite material used in Example 1 is 10W / (mK); the thermal conductivity of the MoS2 / boron nitride two-dimensional composite material used in Example 4 is 6.5w / mk; the thermal conductivity of TFB in Comparative Example 1 is 2.2W / (mK).
[0233] The start-up voltage test method is to use a brightness meter to test the voltage value of the device under 1nits.
[0234] In Table 1, since Example 2 is a blue quantum dot device, the efficiency and life of the blue quantum dot device itself are relatively low. LT95@1000Nit refers to the time required for the device to decay to 950Nit brightness when the initial brightness is 1000nit. The start-up voltage refers to the voltage value when the device brightness is 1nit. Generally, the lower the start-up voltage, the better the carrier recombination.
[0235] Table 1. Performance of each embodiment of this application
[0236]
[0237]
[0238] It can be seen from Table 1 that compared with device comparison examples 1-6, the device embodiments 1-13 of the present application use the improvement of the hole transport layer of the precious metal nanocone array and the two-dimensional material in the embodiments of the present application, so that the external quantum efficiency and the device life are greatly improved, the turn-on voltage is greatly reduced, and the carrier recombination is significantly improved.
[0239] Specifically, by comparing device example 1 with device comparison example 2, it can be seen that the ionic heat generated by the surface plasmons of the noble metal tip structure can effectively increase hole injection, improve the coupled light output of the device, and thus significantly improve the brightness and hole transfer efficiency of the device.
[0240] Through device examples 1 and 13, it can be concluded that conical nanotips are more prone to plasmon excitation than other shapes (such as spherical ones), which enhances the electromagnetic field at the tip and further promotes hole injection, thus having higher device efficiency and better carrier recombination.
[0241] By comparing device example 1 with device comparison example 3, it can be concluded that a hole transport layer composed of two materials alternately stacked is not necessarily sufficient to achieve a better effect. Only a hole transport layer composed of two two-dimensional materials alternately stacked can better achieve carrier injection balance and improve the brightness of the device.
[0242] By comparing device example 1 with device comparison example 4, it can be concluded that the interface modification layer prepared with precious metals has lower ohmic loss in plasma excitation than the interface modification layer prepared with other metals, is more conducive to generating plasma hotspots at the tip apex, and therefore has higher device efficiency, can better achieve carrier injection balance, and improve the brightness of the device.
[0243] By comparing device example 2 with device comparison examples 5-6, it can be concluded that the improvement of the hole transport layer of the present application using a noble metal nanocone array with a two-dimensional material can also produce better technical effects in blue quantum dot devices.
[0244] Device Example 1 uses a graphene / BN two-dimensional composite material with a thermal conductivity of 10 W / (mK); Device Example 4 uses a MoS2 / boron nitride two-dimensional composite material with a thermal conductivity of 6.5 W / mK; and the thermal conductivity of TFB in Comparative Example 1 is 2.2 W / (mK). It can be seen that the hole transport layer using the two-dimensional composite material has a more excellent heat transport performance.
[0245] Furthermore, device embodiment 4 uses molybdenum disulfide / BN as the hole transport layer, wherein the thermal conductivity of molybdenum disulfide is not as good as that of graphene, resulting in a poorer technical effect than the comparative example, but still produces a better technical effect than the single hole transport layer material used in the prior art.
[0246] On the other hand, the smaller the spacing between microspheres, the smaller the spacing of the corresponding metal nanocone array, and the better the effect of generating ion heat. However, if the diameter of the microspheres is too small, the stability of the self-assembled film will be poor and the process difficulty will increase. Therefore, this application uses microspheres with a diameter of 200-300nm as template etching layer materials to prepare corresponding metal nanocone arrays with a spacing of 200-300nm.
[0247] The technical solutions provided by the embodiments of the present application are introduced in detail above. Specific examples are used herein to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the method of the present application and its core idea. At the same time, for technical personnel in this field, according to the idea of the present application, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as a limitation on the present application.
Claims
1. A light emitting device, characterized in that: The invention comprises a first electrode, an interface modification layer, a light-emitting layer and a second electrode which are stacked in sequence; the interface modification layer comprises an interface body and metal protrusions.
2. The light emitting device according to claim 1, characterized in that: The metal protrusion is arranged on the surface of the interface body on a side close to the light-emitting layer; and / or The materials of the interface body and the metal protrusion are independently selected from one or more of gold, silver, and platinum group metals, and the platinum group metals include one or more of iridium, rhodium, palladium, and platinum.
3. The light emitting device according to any one of claims 1 to 2, characterized in that: The light-emitting device further comprises a hole functional layer, wherein the hole functional layer is arranged between the first electrode and the light-emitting layer, the interface modification layer is arranged on a surface of the hole functional layer close to the light-emitting layer, and the convex surface of the metal protrusion faces the light-emitting layer; and / or The metal protrusions include regular-shaped protrusions and / or irregular-shaped protrusions; the regular-shaped protrusions include one or more of metal nano-conical protrusions, metal nano-hemispherical protrusions, metal nano-curved surface protrusions, metal nano-truncated cone protrusions, metal nano-wedge-shaped protrusions, and metal nano-polygonal protrusions; and / or The light-emitting device further comprises an electron transport layer, wherein the electron transport layer is arranged between the light-emitting layer and the second electrode; and / or The diameter of the luminescent nanoparticles in the luminescent layer is 5-10 nm.
4. The light emitting device according to any one of claim 3, characterized in that: The hole functional layer includes a hole transport layer; or The hole functional layer includes a hole injection layer; or The hole functional layer includes a hole injection layer and a hole transport layer. The hole injection layer is arranged between the first electrode and the interface modification layer, and the hole transport layer is arranged between the hole injection layer and the interface modification layer.
5. The light emitting device according to any one of claim 3, characterized in that: The average height of the metal protrusions is 10-20 nm; and / or The average distance between the tops of two adjacent metal protrusions is 20-300 nm; and / or The average diameter or average equivalent diameter of the metal protrusions close to the interface body is 5-10 nm; and / or The average diameter or average equivalent diameter of the metal protrusions in the projected area on the interface body is 5-10 nm; and / or The metal nano-cone-shaped protrusions include metal nano-cone-shaped protrusions and metal nano-pyramid-shaped protrusions, and the metal nano-hemispherical protrusions also include metal nano-semi-ellipsoidal protrusions.
6. The light emitting device according to claim 4, characterized in that: The hole transport layer comprises different types of nanosheets alternately stacked, wherein the different types of nanosheets comprise nanosheets of different thicknesses and / or nanosheets of different materials; and / or The material of the nanosheet includes a two-dimensional material, wherein the two-dimensional material includes one of graphene, boron nitride, molybdenum disulfide, carbon nanotubes, fullerenes, carbon nanosheets, tungsten disulfide, molybdenum diselenide, tungsten diselenide, and MXene; and / or The thickness of the nanosheet is 3-4 nm.
7. The light emitting device according to claim 6, characterized in that: The hole transport layer is composed of two different types of nanosheets stacked alternately.
8. The light emitting device according to claim 4, characterized in that: The first electrode and the second electrode independently include a doped metal oxide particle electrode, a composite electrode, a graphene electrode, a carbon nanotube electrode, a metal single substance electrode or an alloy electrode, the material of the doped metal oxide particle electrode includes one or more of indium doped tin oxide, fluorine doped tin oxide, antimony doped tin oxide, aluminum doped zinc oxide, gallium doped zinc oxide, indium doped zinc oxide, magnesium doped zinc oxide and aluminum doped magnesium oxide, the composite electrode includes one or more of AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, TiO2 / Ag / TiO2, TiO2 / Al / TiO2, ZnS / Ag / ZnS or ZnS / Al / ZnS, and the material of the metal single substance electrode includes one or more of Ag, Al, Cu, Mo, Au, Pt, Ca, Mg and Ba; and / or The material of the electron transport layer includes inorganic materials and / or organic materials; the inorganic material includes one or more of doped or undoped zinc oxide, barium oxide, nickel oxide, titanium oxide, tin oxide, tantalum oxide, zirconium oxide, nickel oxide, lithium titanium oxide, zinc aluminum oxide, zinc manganese oxide, zinc tin oxide, lithium zinc oxide, indium tin oxide, cadmium sulfide, zinc sulfide, molybdenum sulfide, tungsten sulfide, copper sulfide, zinc tin, indium phosphide, gallium phosphide, copper indium sulfide, copper gallium sulfide, and barium titanate, and the doped element includes one or more of aluminum, magnesium, lithium, manganese, yttrium, lanthanum, copper, nickel, zirconium, cerium, and gadolinium; the organic material includes one or more of quinoxaline compounds, imidazole compounds, triazine compounds, fluorene compounds, and hydroxyquinoline compounds; and / or The material of the light-emitting layer includes one or more quantum dot light-emitting materials, and the quantum dot light-emitting materials include one or more of single-structure quantum dots, core-shell quantum dots and perovskite semiconductor materials. The material of the single-structure quantum dots, the core material of the core-shell quantum dots and the shell material of the core-shell quantum dots respectively include at least one of II-VI group compounds, IV-VI group compounds, III-V group compounds and I-III-VI group compounds. The II-VI group compounds include CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSe At least one of Te, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe, and the IV-VI group compound includes SnS, SnSe, SnTe, PbS, PbSe, PbTe , SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe, SnPbSTe, and the III-V group compound includes GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, In At least one of NSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs and InAlPSb, the I-III-VI group compound includes at least one of CuInS2, CuInSe2 and AgInS2, and the perovskite semiconductor material includes a doped or undoped inorganic perovskite semiconductor or an organic-inorganic hybrid perovskite semiconductor. The inorganic perovskite semiconductor has a general structural formula of AMX3, wherein A is Cs + ions, M is a divalent metal cation, including Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ At least one of X is a halogen anion including Cl - Br - ,I - The general structural formula of the organic-inorganic hybrid perovskite semiconductor is BMX3, wherein B is an organic amine cation, including CH3(CH2) n-2 NH3 + or [NH3(CH2) n NH3] 2+ , where n≥2, M is a divalent metal cation, including Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ At least one of X is a halogen anion including Cl - Br - ,I - At least one of; and / or The hole functional layer also includes a hole injection layer, and the material of the hole injection layer includes 4,4'-N,N'-dicarbazolyl-biphenyl, N,N'-diphenyl-N,N'-bis(1-naphthyl)-1,1'-biphenyl-4,4"-diamine, N,N'-diphenyl-N,N'-bis(3-methylphenyl)-(1,1'-biphenyl)-4,4'-diamine, N,N'-bis(3-methylphenyl)-N,N'-bis(phenyl)-spiro, N,N'-bis(4-(N,N'-diphenyl-amino)phenyl)-N,N'-diphenylbenzidine, 4,4',4'-Tris(N-carbazolyl)-triphenylamine, 4,4',4'-tris(carbazolyl-9-yl)triphenylamine, trichloroisocyanuric acid, terbium-doped phosphate-based green luminescent materials, 2,3,6,7,10,11-hexacyano-1,4,5,8,9,12-hexaazatriphenylene, 4,4',4'-tris(N-3-methylphenyl-N-phenylamino)triphenylamine, poly[(9,9'-dioctylfluorene-2,7-diyl)-co-(4,4'-(N-(4-sec-butylphenyl)diphenylamine))], poly(4-butylphenyl-diphenylamine) (poly-TPD), poly[bis(4-phenyl)(4-butylphenyl)amine], polyaniline, polypyrrole, poly(p-phenylene vinylene), poly(phenylene vinylene), poly[2-methoxy-5-(2-ethylhexyloxy)-1,4-phenylene vinylene] and poly[2-methoxy-5-(3',7'-dimethyloctyloxy)-1,4-phenylene vinylene], copper phthalocyanine, aromatic tertiary amines, polynuclear aromatic tertiary amines, 4,4'-bis(p-carbazolyl)-1,1'-biphenyl compounds, N,N,N',N'-tetraarylbenzidine, PEDOT , PEDOT:PSS and its derivatives, PEDOT:PSS derivatives doped with s-MoO3, poly(N-vinylcarbazole) and its derivatives, polymethacrylate and its derivatives, poly(9,9-octylfluorene) and its derivatives, poly(spirofluorene) and its derivatives, N,N'-di(naphthalene-1-yl)-N,N'-diphenylbenzidine, spiro NPB, nano-polycrystalline diamond, microcrystalline cellulose, tetracyanoquinodimethane, doped graphene, undoped graphene, C60, transition metal oxides, transition metal sulfides, and transition metal tin compounds.
9. A method for preparing a light emitting device, characterized in that: The following steps are involved: providing a first electrode; forming a hole functional layer on the first electrode; Forming the interface modification layer in the light-emitting device according to any one of claims 1 to 4 on the hole functional layer; forming a light-emitting layer on the interface modification layer; A second electrode is formed on the light-emitting layer to obtain a light-emitting device.
10. The method for preparing a light emitting device according to claim 9, characterized in that: The hole functional layer includes a hole transport layer and / or a hole injection layer; the hole transport layer or the hole injection layer is arranged between the first electrode and the interface modification layer; or The hole injection layer is disposed between the first electrode and the interface modification layer, and the hole transport layer is disposed between the hole injection layer and the interface modification layer; and / or The interface modification layer comprises an interface body and a metal protrusion, wherein the convex surface of the metal protrusion faces the light-emitting layer; and / or An electronic functional layer is further provided between the light-emitting layer and the second electrode, and the electronic functional layer includes an electron transport layer.
11. The method for preparing a light emitting device according to claim 9, characterized in that: The first electrode is configured as an anode and the second electrode is configured as a cathode; or the first electrode is configured as a cathode and the second electrode is configured as an anode.
12. The method for preparing a light emitting device according to any one of claims 9 to 10, characterized in that: The preparation method of the interface modification layer comprises the following steps: Setting a template etching layer; Prepare metal protrusions by etching the layer through the template; The template etching layer is removed to obtain a layer including at least one metal protrusion, namely, an interface modification layer.
13. The method for preparing a light emitting device according to claim 12, characterized in that: The template etching layer includes a microsphere layer, and the microsphere layer includes one or more of a self-assembled polystyrene microsphere layer and a self-assembled silicon dioxide microsphere layer.
14. The method for preparing a light emitting device according to claim 13, characterized in that: The preparation method of the self-assembled polystyrene microsphere layer comprises: Dissolving the polystyrene microspheres in an organic solvent, and removing the organic solvent after solidification and interface self-assembly reaction; and / or The polystyrene microspheres have a concentration of 10-20% and are disposed on the interface of the hole functional layer, the curing comprises curing at 60-80° C. for 10-30 minutes, the interface self-assembly reaction time is 5-15 minutes, and the removal of the organic solvent comprises heating to 110-170° C.; and / or The organic solvent includes one or more of toluene, dichloromethane, aromatic hydrocarbons, and halogenated hydrocarbons.
15. The method for preparing a light emitting device according to claim 12, characterized in that: The method for removing the template etching layer includes an oxygen reactive etching method, and the oxygen reactive etching method includes: At oxygen flow rate 10-30cm 3 / min and etching power 30-60W, etching for 6-15min.
16. A display device, characterized in that: The display device comprises the light-emitting device according to any one of claims 1 to 8; or, the display device comprises the light-emitting device prepared by the preparation method according to any one of claims 9 to 15.
Citation Information
Cited By
Insulation heat dissipation and electrified visualization three-dimensional hybrid material and preparation method thereof
CN121895860A
Insulating heat-dissipating and live visualizing three-dimensional hybrid material and preparation method thereof
CN121895860B